MyPhyloDB: a local web server for the storage and analysis of metagenomic data. (28th March 2016) - Manter, Daniel K.; Korsa, Matthew; Tebbe, Caleb; Delgado, Jorge A.
Abstract : myPhyloDB v.1.1.2 is a user-friendly personal database with a browser-interface designed to facilitate the storage, processing, analysis, and distribution of microbial community populations (e.g. 16S metagenomics data). MyPhyloDB archives raw sequencing files, and allows for easy selection of project(s)/sample(s) of any combination from all available data in the database. The data processing capabilities of myPhyloDB are also flexible enough to allow the upload and storage of pre-processed data, or use the built-in Mothur pipeline to automate the processing of raw sequencing data. myPhyloDB provides several analytical (e.g. analysis of covariance, t -tests, linear regression, differential abundance (DESeq2), and principal coordinates analysis (PCoA)) and normalization (rarefaction, DESeq2, and proportion) tools for the comparative analysis of taxonomic abundance, species richness and species diversity for projects of various types (e.g. human-associated, human gut microbiome, air, soil, and water) for any taxonomic level(s) desired. Finally, since myPhyloDB is a local web-server, users can quickly distribute data between colleagues and end-users by simply granting others access to their personal myPhyloDB database. myPhyloDB is available at http://www.ars.usda.gov/services/software/download.htm?softwareid=472 and more information along with tutorials can be found on our website http://www.myphylodb.org . Database URL: http://www.myphylodb.org